Analisis Kebijakan Penghapusan Program Akselerasi Menjadi Sistem Kredit Semester (Sks) Kepada Anak Yang Memiliki Potensi Cerdas Istimewa Dan/Atau Berbakat Istimewa (CI-BI) - Ervan Jaya (EduTech: Jurnal Ilmu Pendidikan dan Ilmu Sosial, 2020)
The accelerated program policy is a government-initiated policy in order to facilitate special and special talented children, many studies that have examined the implementation of the accelerated program but in line with the new policy on gifted children are important to be studied. The purpose of this study is to examine how the implementation of the accelerated program, the obstacles that arise in the implementation of the acceleration program and what the background of the acceleration program stops and the emergence of new policies on the SKS system to children who have special intelligence and / or special talent (CI-BI ). This study is based on literature study that aims to find out how the background of birth Semester Credit System to children Special Smart or Gifted (CI-BI). Results From some implementation process can be seen if in running acceleration program there are schools that have run standardized standards both in terms of student recruitment, teacher selection, facilities and infrastructure and implementation of the curriculum, although there is also still need to be improved. Changes to the Accelerated Program Policy to SKS for CI-BI Students needs special attention for the goverment and education practioners